2022
DOI: 10.3390/ijms23168948
|View full text |Cite
|
Sign up to set email alerts
|

N-Octyl Caffeamide, a Caffeic Acid Amide Derivative, Prevents Progression of Diabetes and Hepatic Steatosis in High-Fat Diet Induced Obese Mice

Abstract: The underlying pathological mechanisms of diabetes are complicated and varied in diabetic patients, which may lead to the current medications often failing to maintain glycemic control in the long term. Thus, the discovery of diverse new compounds for developing medicines to treat diabetes and its complications are urgently needed. Polyphenols are metabolites of plants and have been employed in the prevention and treatment of a variety of diseases. Caffeic acid phenethyl ester (CAPE) is a category of compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Herein, the lower level of caffeamide derivative 36M treatment for 72 h presented a more potent ability to induce cell toxicity in cancer cells than the corresponding dose level of the CAPE derivative 26G ( Figure 1 A,B). This study indicates that 36M plays critical roles in preventing type 2 diabetes and oral microbes because of its broad resistance to acid, alkali, and high-temperature conditions [ 27 , 28 ]. Furthermore, 36M showed more potent cell cytotoxicity than other CAPE derivatives [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, the lower level of caffeamide derivative 36M treatment for 72 h presented a more potent ability to induce cell toxicity in cancer cells than the corresponding dose level of the CAPE derivative 26G ( Figure 1 A,B). This study indicates that 36M plays critical roles in preventing type 2 diabetes and oral microbes because of its broad resistance to acid, alkali, and high-temperature conditions [ 27 , 28 ]. Furthermore, 36M showed more potent cell cytotoxicity than other CAPE derivatives [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAPE and caffeamide derivatives ( 26G , 36C , 36H , 36 K , and 36M ) were synthesized and provided by Dr. Yueh-Hsiung Kuo, and the extraction processes were as reported previously [ 27 , 45 ]. Briefly, benzotriazol-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate was dissolved in dichloromethane and added to a mixture of caffeic acid, phenethyl alcohol, corresponding amines, and triethylamine in dimethylformamide.…”
Section: Methodsmentioning
confidence: 99%
“…In-vivo studies in highfat-induced obese animal models also evaluated the compound's involvement in slowing diabetes progression via AMPK regulation. This compound indirectly reduces insulin resistance, improves GLUT4 transport, and may work as a potential treatment for Type 2 DM (Wu et al 2022). Numerous CAPE derivatives studied for their cytotoxicity showed a 3-16% drop in viable cells while simultaneously improving glucose absorption by about 70% (Eid et al 2010).…”
Section: Caffeic Acid Phenolic Derivative (Noctyl Caffeamide)mentioning
confidence: 99%
“…[4] Caffeic acid derivatives such as caffeic acid ester and caffeamide have been widely used as templates to develop novel therapeutic candidates based on their pluripotent biological activities against diverse human diseases. [5][6][7] In addition to their wide range of therapeutic properties including anti-Parkinson's disease [8] and anti-diabetic effects, [9] natural and synthetic caffeamide derivatives have several advantages over their ester analogs, such as metabolic stability. For instance, Yang et al reported that caffeic acid phenethyl amide, an amide surrogate of caffeic acid phenethyl ester (CAPE), a bioactive component of propolis, showed a prolonged in-vivo half-life by avoiding enzymatic hydrolysis without significant changes in its cytoprotective properties compared to those of CAPE.…”
Section: Introductionmentioning
confidence: 99%